2016
DOI: 10.35196/rfm.2016.1.67-77
|View full text |Cite
|
Sign up to set email alerts
|

HETEROSIS DE CRUZAS ENTRE LINEAS DE TOMATE (Solanum lycopersicum L.) NATIVO MEXICANO TIPO PIMIENTO Y LINEAS TIPO SALADETTE

Abstract: En México el tomate o jitomate (Solanum lycopersicum L.) es una de las hortalizas de mayor importancia por su superficie cultivada, por las divisas y el número de empleos que genera, y por su valor alimenticio y cultural. Sin embargo, el material nativo mexicano “criollo” se ha estudiado poco en cuanto a su rendimiento, calidad, resistencia a factores bióticos y abióticos, y en su potencial como fuente de germoplasma en programas de mejoramiento genético. En este trabajo se evaluó el comportamiento heterótico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In relation to DFR1, the 89 advanced lines behaved similarly to the commercial control, with flowering times ranging from 55 to 68 days from planting. This indicates that the first flower emergence was recorded on day 26 after transplanting, which is apparently earlier than what was observed by Vázquez-Martínez et al (2016), who recorded the beginning of flowering on day 76 after planting, i.e., 34 days after transplanting, in the F 2 that generated the current advanced lines. This is mainly attributed to the differences in planting dates and locations (Carrillo-Rodríguez et al, 2013) between studies, as both cases included the hybrid "El Cid" as a control, with the genotypes flowering similarly to the control.…”
Section: Means Comparison Of Advanced Linesmentioning
confidence: 50%
See 3 more Smart Citations
“…In relation to DFR1, the 89 advanced lines behaved similarly to the commercial control, with flowering times ranging from 55 to 68 days from planting. This indicates that the first flower emergence was recorded on day 26 after transplanting, which is apparently earlier than what was observed by Vázquez-Martínez et al (2016), who recorded the beginning of flowering on day 76 after planting, i.e., 34 days after transplanting, in the F 2 that generated the current advanced lines. This is mainly attributed to the differences in planting dates and locations (Carrillo-Rodríguez et al, 2013) between studies, as both cases included the hybrid "El Cid" as a control, with the genotypes flowering similarly to the control.…”
Section: Means Comparison Of Advanced Linesmentioning
confidence: 50%
“…These results confirm the potential for high yield of the new advanced lines, particularly those from initial crosses with the commercial hybrid Cuauhtémoc. Vázquez-Martínez et al (2016) found that the best initial crosses for the total weight of fruits involved native parents LOR111, LOR81, LOR79, LOR84, and LOR103 with commercial parents R and C. This study shows that the yields of the outstanding advanced lines involved the same commercial parents. However, three of those nine lines are from LOR85, indicating that it is a native parent that combines favorably with the parents from commercial hybrids.…”
Section: Means Comparison Of Advanced Linesmentioning
confidence: 59%
See 2 more Smart Citations